Analisis Kawasan Rawan Longsor dan Keterkaitannya terhadap Kualitas Tanah dan Penggunaan Lahan (Kasus di Kawasan Agribisnis Juhut Kabupaten Pandeglang) - Hasmana Soewandita (Jurnal ALAMI : Jurnal Teknologi Reduksi Risiko Bencana, 2018)
AbstractJuhut region based on the government policy of Banten Province in 2015 is an area that will be developed as a center of agribusiness development area. Its existence is located on the slopes of the hills and at the same time as a residential area allegedly as an area prone to landslides. Agriculture cultivation activities related to soil fertility conditions that are on the belt of the volcano, making this area attracts the community to conduct agricultural cultivation activities despite being on a slope land. The aims of this study are the biophysical analysis of landslide hazard areas and their relationship to soil quality and land use patterns.The method used in this study is observation and groundceck of field biophysical condition and overlay analysis of thematic map related to landslide prone condition. The results of the study indicate that the biophysical condition of the land indicates that the landslide prone areas are susceptible to 707.1 Ha (70%), while the high vulnerability area reaches 245.3 Ha (24%). Soil fertility causes attractive soil to be managed by the community for the cultivation of seasonal crops or horticultural crops that can further trigger a landslide. This is also because the soil type conditions also have physical properties that are vulnerable to the early behavior of seasonal changes (from dry season to rainy season).Â  Land use that is not suitability with morphological conditions of land and already managed by the community as an economic source will be a threat of high vulnerability to landslide hazards.Keywords :Â  agribisnis area, land slides hazard, soil biophysical, land quality